Management of the sick neonate in the field. (2nd July 2019) - Redpath, Adam; Bailey, James
Abstract : The sick foal provides a variety of challenges in ambulatory practice. A problem-based approach allows for the management of multifactorial conditions and the identification of those that require immediate hospitalisation. Diseases that present from birth include congenital abnormalities (atresia of the colon, cleft palate, ventricular septal defects), disorders acquired in-utero (meconium aspiration, pneumonia), those related to gestational age (prematurity and dysmaturity) and those associated with parturition (asphyxia, rib fractures). Disorders that develop in foals that were normal at birth include neonatal maladjustment, sepsis, meconium impactions, neonatal isoeyrthrolysis, bladder rupture, omphalophlebitis and musculoskeletal disorders. Protocols for diagnosis and management applicable to a field setting are described.